2005
DOI: 10.1017/s0021859605004958
|View full text |Cite
|
Sign up to set email alerts
|

The possible use of n-alkanes, long-chain fatty alcohols and long-chain fatty acids as markers in studies of the botanical composition of the diet of free-ranging herbivores

Abstract: SU MMARYFew methods exist for estimating quantitatively the diet composition of free-ranging herbivores. The current study examined whether long-chain fatty alcohols (alcohols) or long-chain fatty acids (acids) could be used along with n-alkanes to allow reliable diet composition estimates to be made in herbivores consuming complex diets. Twelve Scottish Blackface wether sheep housed in metabolism crates were fed four different mixtures of three plant species (three animals per mixture) for a sevenperiod exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 20 publications
12
50
0
Order By: Relevance
“…In comparison with LCFA, LCOH showed lower total concentrations as observed by Ferreira et al (2015) with similar plant species. A similar trend was observed by Ali et al (2005) when comparing the concentration of these epicuticular wax compounds on 25 rangeland species of Sudan. By contrast, Lin et al (2009 and found a predominance of LCOH over LCFA in several Chinese grass species and other forages such as Chenopodium album, Medicago sativa and Bromus inermis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In comparison with LCFA, LCOH showed lower total concentrations as observed by Ferreira et al (2015) with similar plant species. A similar trend was observed by Ali et al (2005) when comparing the concentration of these epicuticular wax compounds on 25 rangeland species of Sudan. By contrast, Lin et al (2009 and found a predominance of LCOH over LCFA in several Chinese grass species and other forages such as Chenopodium album, Medicago sativa and Bromus inermis.…”
Section: Discussionsupporting
confidence: 82%
“…In these situations, Ferreira et al (2009a) suggested that the combination of several faecal markers (alkanes, LCFA and LCOH) can provide a more specific fingerprint to each plant species, increasing the discriminatory power between them. To the authors' knowledge, there are no published studies using LCOH as markers for horses, previous studies with small ruminants (Ali et al, 2005;Lin et al, 2009 andFerreira et al, 2012 and2015) also observed greater accuracy when LCOH were used, compared with alkanes and LCFA. By contrast, Dove and Charmley (2008) obtained better estimates of diet composition of sheep when using alkanes compared with LCOH, due to high correlation between the LCOH profiles of two of the forage components (Phalaris aquatica and ryegrass).…”
Section: Diet Composition Estimatesmentioning
confidence: 86%
See 1 more Smart Citation
“…However, in some tropical grasses the concentrations of important alkanes may decrease markedly with increasing age of leaves (Laredo et al, 1991); this is of concern as the method depends on estimation of alkane concentration in the leaf ingested. A further difficulty is that some tropical forages and edible browses contain very low concentrations of alkanes (Laredo et al, 1991;Ali et al, 2005) so that the presence of these plant species in the diet could not be measured from faecal alkane concentrations. Even if these constraints associated with the markers can be overcome, a further consideration is that tropical native pasture grassland systems often contain a very large and diverse range of edible plant species.…”
Section: Evaluation Of Pasture Attributesmentioning
confidence: 99%
“…This resulted in reduced accuracy of intake estimation in diets containing large proportions of phalaris. In that study, we suggested (Charmley and Dove, 2007) that the accuracy of estimation of diet composition, and thus forage intake, could be increased by also using other cuticular wax markers such as the long-chain alcohols (LCOH), in the estimation of diet composition (Bugalho et al, 2004;Ali et al, 2005;Dove and Mayes, 2005).…”
Section: Introductionmentioning
confidence: 99%